UN’APPLICAZIONE ARCGIS PER LA SICUREZZA DEL COSTRUITO - Colombo, Luigi; Marana, Barbara (GEOmedia, 2013)
La difesa delle città da eventi naturali, come i terremoti, richiede sia il miglioramento delle qualità costruttive degli edifici, sia la riduzione consistente della loro danneggiabilità . Questi requisiti sono conseguibili, per gli edifici di nuova costruzione, attraverso l'applicazione della normativa anti-simica, e, per quelli esistenti, utilizzando strumenti che si basano su un'attenta classificazione della predisposizione al danneggiamento (vulnerabilità ), sia per l'aspetto costruttivo sia per quello strutturale, materico e geo-ambientale. The Italian land has a great amount of both ancient outstanding buildings and modern ones. Nowadays, risk evaluation and analysis are extremely useful to prevent the dangerous natural calamities, which have always been happening in Italy, involving both human lives and structures maintenance. This is a very complex problem which requires a wide knowledge concerning structural, material and territorial information: a GIS system could be the effective instrument able to automatize analysis processes, to provide thematic outputs and to help the users in operational choices and online analyses. The paper deals with a GIS application in the little town of Verdellino, close to Bergamo, which has been developed carrying out a detailed geo-database for seismic buildings classification. The experience has proved the meaningful role of informatics instruments in visualization, risk classification and in pre/ post events management for a more general safeguard.